2007
DOI: 10.1038/sj.leu.2404798
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of parathyroid hormone-related protein promoter P2 by NF-κB in adult T-cell leukemia/lymphoma

Abstract: Parathyroid hormone-related protein (PTHrP) plays a primary role in the development of humoral hypercalcemia of malignancy (HHM) that occurs in the majority of patients with adult T-cell leukemia/lymphoma (ATLL) due to human T-cell lymphotropic virus type-1 (HTLV-1) infection. We previously showed that ATLL cells constitutively express high levels of PTHrP via activation of promoters P2 and P3, resulting in HHM. In this study, we characterized a nuclear factor-jB (NF-jB) binding site in the P2 promoter of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…5 Although PTHrP is likely very important in ATLL, the concentrations of PTHrP in the serum do not always correlate with the degree of hypercalcemia in ATLL patients, suggesting that other factors are involved in the development of HHM. In our study, we carried out real-time RT-PCR and ELISA and found high expression of MIP-1a in RV-ATL cells and increased MIP-1a in the plasma of mice bearing RV-ATL-luc cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Although PTHrP is likely very important in ATLL, the concentrations of PTHrP in the serum do not always correlate with the degree of hypercalcemia in ATLL patients, suggesting that other factors are involved in the development of HHM. In our study, we carried out real-time RT-PCR and ELISA and found high expression of MIP-1a in RV-ATL cells and increased MIP-1a in the plasma of mice bearing RV-ATL-luc cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NF-nB binding sites were found in the promoters of parathyroid hormone-related protein (PTHrP; refs. 5,6) and macrophage inflammatory protein 1a (MIP-1a; ref. 7).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of trans ‐activation of the promoter of the PTHLH gene was demonstrated in a plasmid‐construct transfection model (Watanabe et al , 1990). More recently it was demonstrated that nuclear factor kappa B (NF‐κB) can upregulate PTHLH transcription in ATLL cells by a tax ‐independent mechanism (Nadella et al , 2007).…”
Section: Hypercalcaemia In Haematological Disordersmentioning
confidence: 99%
“…In adult T cell leukemia/lymphoma (ATLL) it was shown that the PTHrP promoter 2, which is upregulated in ATLL as well, contains a binding site for nuclear factor κB (NFκB), to which the subunits p50 and c-Rel bind in vivo. 35 Transient co-transfection with NFκB expression plasmids and PTHrP P2 luciferase reporterplasmid, showed that different combinations of the subunits cooperatively upregulated the PTHrP P2 promoter, while inhibition of NFκB activity reduced PTHrP P2 promoter-initiated transcription indicating a crucial role for NFκB in the regulation of the P2 in ATLL. It remains to be demonstrated if a similar mechanism can also account for the observed activation of P2 correlating with the invasiveness of our breast cancer cell line model.…”
Section: Discussionmentioning
confidence: 98%